Meta-analysis of individual and combined effects of mycotoxins on growing pigs - Andretta, Ines; Kipper, Marcos; Hauschild, Luciano [UNESP]; Lehnen, Cheila Roberta; Remus, Aline [UNESP]; Melchior, Raquel (Univ Sao Paolo, 2016)
Little is known about the toxicity of concomitantly occurring mycotoxins in pig diets. This study was conducted to evaluate, through meta-analysis, the individual and the combined effects of mycotoxins on pig performance. The meta-analysis followed three sequential analyses (graphical, correlation, and variance-covariance) based on a database composed of 85 published papers, 1,012 treatments and 13,196 animals. Contamination of diets with individual mycotoxins reduced (p < 0.05) feed intake by 14 % and weight gain by 17 %, while combined mycotoxins reduced the same responses by 42 % and 45 %, respectively, in comparison with the non-challenged group. The correlation (p < 0.05) between reduction in weight gain (Delta G) and reduction in feed intake (Delta FI) was 0.67 in individual challenges and 0.93 in combined challenges. The estimated Delta G was -6 % in individual challenges and -7 % in combined challenges when Delta FI was zero, suggesting an increase in the maintenance requirements of challenged animals. Most of Delta G (58 % in individual challenges and 84 % in combined challenges) was attributed to the changes in feed efficiency. The association of mycotoxins enhances individual toxic effects and the.FI is important in explaining the deleterious effects on the growth of challenged pigs.
Keywords: modelling; sanitary challenge; swine; toxicology